Pediatric Bulbar and Posterior Urethral Injuries: Operative Outcomes and Long-Term Follow-Up - Trachta, Jan; Moravek, Jiri; Kriz, Jan; Padr, Radek; Skaba, Richard (European Journal of Pediatric Surgery, 2016)
Aim The aim of this study was to analyze complications and outcomes of end-to-end urethral anastomosis performed for posttraumatic bulbar strictures or posterior urethral injuries in pediatric patients.Methods The records of 15 boys, age 18 years and below, admitted to our tertiary trauma center with urethral injuries from 1989 to 2014 were reviewed retrospectively. Out of these 15 boys, 7 were excluded (2 for iatrogenic trauma, 2 for minor straddle injuries who were not operated on, 2 for incomplete records, and 1 lost to follow-up) and 8 analyzed patients were operated for bulbar or posterior urethral injury. The mean follow-up after the operation was 4.5 years (range 0.5–10). To obtain up-to-date follow-up information, all the analyzed patients were contacted by a letter and telephone in January 2015 and asked about lower urinary tract or erectile dysfunction (ED) using the International Index of Erectile Function-5 questionnaire.Results Mean age at the time of injury was 12.3 years (range 5–17). Four patients with pelvic fracture had complete posterior urethra disruption, three patients after straddle injury developed obliterating stricture of the bulbar urethra and one patient had torn his bulbar urethra apart by a sharp hook. Except for the immediate exploration of the open perineal wound, all patients were operated via perineal approach 1 to 6 months after initial suprapubic catheter insertion. Five patients needed a cystotomy to identify the proximal urethral stump by a probe, and two patients had partial pubectomy to gain urethral length. Postoperative complications included stricture in anastomosis in six patients (all reoperated, four more than once including attempts of endoscopic internal urethrotomy). Six days after surgery, one patient developed massive external bleeding around a permanent urinary catheter due to a posttraumatic ruptured arterial aneurysm that was later stopped by urgent angiography and coil insertion. After discharge, three patients had transient stress incontinence. All patients had uroflowmetry maximum flow above 20 mL/s on their last follow-up except for two (12 and 15 mL/s). None have any lower urinary tract dysfunction symptoms in adulthood; one suffers from mild ED and two report moderate ED due to penile shortening.Conclusion Delayed end-to-end anastomosis for pediatric urethral injury is a safe operational option. However, high rate of short-term complications and reoperations should be expected. Penile shortening is one of the most severe long-term complications.
Keywords: urethra; pelvic fracture; urethral stricture; erectile dysfunction